TRANSOMIZED PLACE NAMES IN KUMKURGAN DISTRICT - Torayeva Sayyora Bakhtyorovna (Galaxy International Interdisciplinary Research Journal, 2023)
One of the important features and laws of toponymy is the phenomenon of name transfer - transonymization. In this article, transomized place names in Kumkurgan district of Surkhandarya region were analyzed.